An overview of existing modeling tools making use of model checking in the analysis of biochemical networks - Carrillo, Miguel; Góngora, Pedro A.; Rosenblueth, David A. (Frontiers in Plant Science, 2012)
Model checking is a well-established technique for automatically verifying complex systems. Recently, model checkers have appeared in computer tools for the analysis of biochemical (and gene regulatory) networks. We survey several such tools to assess the potential of model checking in computational biology. Next, our overview focuses on direct applications of existing model checkers, as well as on algorithms for biochemical network analysis influenced by model checking, such as those using binary decision diagrams or Boolean satisfiability solvers. We conclude with advantages and drawbacks of model checking for the analysis of biochemical networks.